2018
DOI: 10.1104/pp.18.01075
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CER1-LIKE1 Functions in a Cuticular Very-Long-Chain Alkane-Forming Complex

Abstract: Plant aerial organs are coated with cuticular waxes, a hydrophobic layer that primarily serves as a waterproofing barrier. Cuticular wax is a mixture of aliphatic very-long-chain molecules, ranging from 22 to 48 carbons, produced in the endoplasmic reticulum of epidermal cells. Among all wax components, alkanes represent up to 80% of total wax in Arabidopsis (Arabidopsis thaliana) leaves. Odd-numbered alkanes and their derivatives are produced through the alkane-forming pathway. Although the chemical reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 56 publications
1
74
0
Order By: Relevance
“…All these genes showed constant transcript levels but were strongly repressed at the protein level in russet fruit skin compared with green fruit skin of sand pear 23.1.199, EC: 1.1.1330, and EC: 1.3.1.93) inhibited the biosynthesis of long chain fatty acids, providing substrates for the biosynthesis of cutin, wax, and suberin. CER1 is a core component of the complex controlling very-longchain alkane synthesis [40][41][42] . CYP86A4 plays a key role as a cutin ω-hydroxylase in the biosynthesis of 16-hydroxypalmitate, 10,16-dihydroxypalmitate, and 1,16-hexadecanedioic acid 43 .…”
Section: Metabolic Characteristics and Abiotic Stress-responsive Genementioning
confidence: 99%
“…All these genes showed constant transcript levels but were strongly repressed at the protein level in russet fruit skin compared with green fruit skin of sand pear 23.1.199, EC: 1.1.1330, and EC: 1.3.1.93) inhibited the biosynthesis of long chain fatty acids, providing substrates for the biosynthesis of cutin, wax, and suberin. CER1 is a core component of the complex controlling very-longchain alkane synthesis [40][41][42] . CYP86A4 plays a key role as a cutin ω-hydroxylase in the biosynthesis of 16-hydroxypalmitate, 10,16-dihydroxypalmitate, and 1,16-hexadecanedioic acid 43 .…”
Section: Metabolic Characteristics and Abiotic Stress-responsive Genementioning
confidence: 99%
“…It is well established in model plant Arabidopsis (Arabidopsis thaliana) that cuticular wax biosynthesis begins with the esterification of CoA to the plastid-derived C 16 and C 18 fatty acids by long-chain acyl-CoA synthetase proteins in the endoplasmic reticulum (ER), and the generated C 16 and C 18 acyl-CoAs are elongated to VLC acyl-CoAs under the action of the fatty acid elongase complex and ECERIFERUM2 proteins (Xia et al, 1996;Todd et al, 1999;Fiebig et al, 2000;Hooker et al, 2002;Schnurr et al, 2004;Zheng et al, 2005;Bach et al, 2008;Beaudoin et al, 2009;Lee et al, 2009;Lü et al, 2009;Weng et al, 2010;Haslam et al, 2012;Haslam and Kunst, 2013;Kim et al, 2013;Haslam et al, 2015). The elongated VLC acyl-CoAs are then modified into aldehydes, alkanes, secondary alcohols, and ketones by an alkane-forming pathway, or into primary alcohols and wax esters by an alcoholforming pathway (Aarts et al, 1995;Millar et al, 1999;Chen et al, 2003;Rowland et al, 2006Rowland et al, , 2007Greer et al, 2007;Bourdenx et al, 2011;Bernard et al, 2012;Yang et al, 2017;Pascal et al, 2019). As a core component of fatty acid elongase complex, enoyl-CoA reductase (ECR) catalyzes the final step in the biosynthesis of VLC acyl-CoAs (Zheng et al, 2005).…”
mentioning
confidence: 99%
“…In the decarbonylation pathway, VLC-acyl-CoAs are catalyzed into alkanes by an ER-localized CER1, CER3 and cytochrome B5 complex [33]. It was recently reported that the CER1 homolog, CER1-LIKE1, was also involved in alkane formation [44]. Subsequently, alkanes are oxidized into secondary alcohols and ketones by the midchain alkane hydroxylase 1 (MAH1) [34].…”
Section: Discussionmentioning
confidence: 99%